2021
DOI: 10.3390/ani11041094
|View full text |Cite
|
Sign up to set email alerts
|

How Tourist Preference and Satisfaction Can Contribute to Improved Welfare Standards at Elephant Tourism Venues in Thailand

Abstract: Consumer satisfaction and preference can be integral in influencing and solidifying change in user-driven industries such as tourism. High satisfaction rates are imperative to the continual success of a venue as satisfaction determines the likelihood of repeat business and positive recommendations to friends, family and online review forums. Tourist preference for ecocentric tourism venues, over anthropocentric ones, appears to be increasing in elephant tourism venues (ETVs) in Thailand. To explore this, we vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The implementation of an interpretation program in order to introduce biodiversity and ecosystems, as well as culture around the national park area to tourists requires certain tools and methods as shown in Table 4. The use of various tools and methods is carried out in order to arouse feelings of wonder, awe, empathy, and concern audiences (Wolf & Croft, 2012;Lück, 2016;Tiberghien & Lennon, 2019;Dell'Eva et al, 2020;Tan & Choy, 2020;Ballantyne et al, 2021;Flower et al, 2021;Zhu et al, 2021). Traveling around is a method favored by many audiences in the TNGHS area, in this way tourists can enjoy open spaces and enrich their experiences in the national park area (Piccininni et al, 2018;Hudson, 2016).…”
Section: Tourist Community Managermentioning
confidence: 99%
See 3 more Smart Citations
“…The implementation of an interpretation program in order to introduce biodiversity and ecosystems, as well as culture around the national park area to tourists requires certain tools and methods as shown in Table 4. The use of various tools and methods is carried out in order to arouse feelings of wonder, awe, empathy, and concern audiences (Wolf & Croft, 2012;Lück, 2016;Tiberghien & Lennon, 2019;Dell'Eva et al, 2020;Tan & Choy, 2020;Ballantyne et al, 2021;Flower et al, 2021;Zhu et al, 2021). Traveling around is a method favored by many audiences in the TNGHS area, in this way tourists can enjoy open spaces and enrich their experiences in the national park area (Piccininni et al, 2018;Hudson, 2016).…”
Section: Tourist Community Managermentioning
confidence: 99%
“…Several studies have shown that the use of guide services can provide more satisfaction for visitors than the use of audio or self-guided (Moscardo, 2017;Beattie & Schneider, 2018), and direct experience in natural conditions is considered important by visitors (Lück, 2016;Muneenam et al, 2017;Dell'Eva et al, 2020;Farkic et al, 2021;Flower et al, 2021). One of the considerations that can improve services to visitors in the national park area is by involving more interpreters in the national park area (Dileep Kumar et al, 2020).…”
Section: Tourist Community Managermentioning
confidence: 99%
See 2 more Smart Citations
“…In the original manuscript, there was an opening bracket before the "e,g.," range of activities. Animals are used as transport for both people and equipment; for example, yaks in Nepal (Ning, Oli, Gilani, Joshi, & Bisht, 2016), mules in Morocco (Cousquer & Allison, 2012), camels in Botswana (Seiful, Angassa, & Boitumelo, 2019), horses in Iceland (Helgadóttir & Dashper, 2016), sled dogs in Canada (Fennell & Sheppard, 2011), and elephants in Thailand (Flower, Burns, & Jones, 2021).…”
Section: Animals As Workers In the Ecotourism Industrymentioning
confidence: 99%